Sistem Pendukung Keputusan Perbandingan Metode MOORA Dengan MOOSRA Dalam Pemilihan Hair Stylish - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
This study aims to compare the effectiveness of the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis) and MOOSRA (Multi-objective Optimization on the Basis of Simple Ratio Analysis) methods in the context of selecting stylish hair at the barbershop. In the growing hair care industry, the selection of stylish hair does not only affect the appearance of the customer but also plays an important role in the image and success of the barbershop itself. Therefore, it is important for barbershop owners to choose the right stylish hair. The MOORA method is known for its ability to solve multi-objective decision-making problems by utilizing ratio analysis. Meanwhile, MOOSRA is another method that focuses on optimization by considering relative preferences. In the context of selecting stylish hair, both can be useful tools in guiding barbershop owners to choose stylish hair according to customer needs and preferences. This research involves collecting data regarding customer preferences and hair stylish characteristics from various barbershops. This data was then analyzed using the MOORA and MOOSRA methods to choose the most suitable hair style for each scenario. The results of the analysis will be compared to assess the relative performance of the two methods in this context. It is hoped that the results of this research will provide valuable insights for barbershop owners and the hair care industry in general. By understanding the advantages and limitations of each method, barbershop owners will be able to make more informed decisions in selecting stylish hair. In addition, this research can also contribute to the development of a methodology in more complex multi-objective decision-making, by providing concrete examples in practical applications. The final results of the calculations of the two methods are proven to produce the same highest ranking result, which is obtained by alternative 1 on behalf of Poppy Sukma.